2010
DOI: 10.1097/pai.0b013e3181acaded
|View full text |Cite
|
Sign up to set email alerts
|

Are the Pure In Situ Breast Ductal Carcinomas and Those Associated With Invasive Carcinoma the Same?

Abstract: It has been reported that pure ductal carcinoma in situ of the breast has morphologic differences from the in situ component of the invasive ductal carcinoma, as well estrogen and progesterone receptors expression according to their cytokeratin expression. However, there is no data comparing other tumor markers without using the cytokeratin expression. The objective of this study is to compare the expression of estrogen receptor (ER) and progesterone receptor (PR), HER-2/neu, p53, and Ki67 between pure ductal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 10 publications
1
10
0
Order By: Relevance
“…The similarities between the expressions of these tumor markers suggest that these tumors belong to the same cellular clone in different phases of their growth, and the in situ components may represent cells with a higher potential of malignancy. These findings are in agreement to those reported by Schuetz et al, [19] where they identified the similarities between the gene expression of the in situ and invasive components of the same tumor by using microarray hierarchical cluster analysis, and with others [20,21].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The similarities between the expressions of these tumor markers suggest that these tumors belong to the same cellular clone in different phases of their growth, and the in situ components may represent cells with a higher potential of malignancy. These findings are in agreement to those reported by Schuetz et al, [19] where they identified the similarities between the gene expression of the in situ and invasive components of the same tumor by using microarray hierarchical cluster analysis, and with others [20,21].…”
Section: Discussionsupporting
confidence: 92%
“…Tumor markers: Tumor markers are molecules occurring in tissue that are associated with cancer and whose identification is useful in patient diagnosis and treatment or clinical management [17]. In this study, we compared the immunohistochemical expression of tumor markers (ER, PR, HER-2/neu, P53) between breast ductal carcinoma (IDC+NIDC), without sub typing into low and high grade, as it was carried out by Mario et al, [18] versus benign breast lesions. Moreover, we compared the immunohistochemistry expression of these markers within the different breast tumors (ie, IDC, NIDC), as well as, with clinicopathological features of these lesions.…”
Section: Discussionmentioning
confidence: 99%
“…The concordant expression of immunohistochemical 11 14 and genomic 15 17 markers supports the clonal relationship between breast DCIS and IDC-DCIS. However, survival in patients with DCIS in breast IDC remains uncertain.…”
Section: Introductionmentioning
confidence: 54%
“…Several studies have shown no differences in the biomarker expression in the DCIS component of IBCA versus IBCA only [17, 35]. We did not include basal markers for further characterization of the triple negative tumors.…”
Section: Discussionmentioning
confidence: 99%